Analisis Profitabilitas dan Efisiensi Operasional pada Industri Perikanan Skala Kecil di Indonesia - Marlina, Marlina; Haja Almuqaramah., T.M Haja Almuqaramah; Rusmina, Cut Rusmina; Rahmi, Rahmi; Zidane, Muhammad (Jurnal Serambi Engineering, 2025)
The small-scale fisheries industry in Indonesia plays a crucial role in food security and local economic resilience. However, the industry continues to face challenges in profitability and operational efficiency. This study employs a literature review approach to analyze the performance of small-scale fisheries through profitability indicators (net profit margin, return on assets, or ROA) and operational efficiency (input-output ratio, data envelopment analysis, or DEA). The findings indicate a positive correlation between technical efficiency and increased profit margins. The identified key barriers to financial inclusion include low financial literacy, limited technology access, and restricted market reach. Conversely, cooperatives, technical training, and business digitalization have emerged as pivotal enabling factors. This study proposes a data-driven policy approach and multi-stakeholder collaboration as a means of enhancing competitiveness and sustainability in this sector. When implemented with strategic precision, small-scale fisheries have the potential to transform into a robust component of the coastal economy, achieving global competitiveness.